Unwrapping differential x-ray phase-contrast images through phase estimation from multiple energy data - Epple, F. M.; Potdevin, G.; Thibault, Pierre; Ehn, S.; Herzen, Julia; Hipp, A.; Beckmann, Felix; Pfeiffer, F. (Optics Express, 2013)
We present a spectral phase unwrapping approach for grating-based differential phase-contrast data where the unwrapped interferometer phase shift is estimated from energy discriminated measurements using maximum likelihood principles. We demonstrate the method on tomographic data sets of a test specimen taken at different x-ray energies using synchrotron radiation. The proposed unwrapping technique was demonstrated to successfully correct the data set for phase wrapping. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2023-03-08